Jawabanmu

2014-04-26T01:05:55+07:00
Lim  √(x²+x-1)-√(2x-1)=  lim  (√(x²+x-1)-√(2x-1))(√(x²+x-1)+√(2x-1)(√(x+3) + 2)
                                   x⇒1((√(x + 3) -2)(√(x²+x-1)+√(2x-1))(√(x+3) + 2)
                               = lim     (x² + x - 1 - 2x + 1)(√(x + 3) + 2)
                                 x⇒1    (x + 3 - 4)(√(x² + x - 1) + √(2x - 1))
                               = lim     (x² - x)(√(x + 3) + 2)
                                 x⇒1  (x -1)(√(x² + x - 1) + √(2x - 1))
                              =  lim     x(x - 1)(√(x + 3) + 2)
                                 x⇒1  (x -1)(√(x² + x - 1) + √(2x - 1))

                              =  lim     x(√(x + 3) + 2)
                                 x⇒1  (√(x² + x - 1) + √(2x - 1))
                             = 1(√(1 + 3) + 2
                               √(1²+1-1) + √(2 -1)
                             = 2 + 2
                                1 + 1
                             = 4/2
                             = 2